Given : "\\mathbf{f(x)=\\dfrac{1-x}{1+x}}"
"\\mathbf{f(-x)=\\dfrac{1-(-x)}{1+(-x)}=\\dfrac{1+x}{1-x}}"
2."\\;for\\;f(x+1)\\;,replace\\;x\\;by\\;(x+1)\\;in\\;f(x),\\;then"
"\\mathbf{f(x+1)=\\dfrac{1-(x+1)}{1+(x+1)}=\\dfrac{1-x-1}{1+x+1}=\\dfrac{-x}{2+x}}"
3."\\;for\\;f(x)+1,\\;we\\;have-"
"\\mathbf{f(x)+1=\\dfrac{1-x}{1+x}+1=\\dfrac{1-x+(1+x)}{1+x}=\\dfrac{2}{1+x}}"
4."\\;" "for\\;f(1\/x)\\; ,replace\\;x\\;by\\;(1\/x)\\;in\\;f(x),\\;then"
"\\mathbf{f(1\/x)=\\dfrac{1-\\dfrac{1}{x}}{1+\\dfrac{1}{x}}=\\dfrac{\\dfrac{x-1}{x}}{\\dfrac{x+1}{x}}=\\dfrac{x-1}{x+1}}"
5."\\;\\;for\\;1\/f(x),\\;we\\;have-"
"\\mathbf{\\dfrac{1}{f(x)}=\\dfrac{1}{\\dfrac{1-x}{1+x}}=\\dfrac{1+x}{1-x}}"
Comments
Leave a comment